The Essence of Effective and Efficient Learning - Syafaruddin, Baso; Dirhamzah, Dirhamzah (Universitas Islam Negeri Alauddin Makassar, 2020)
To realize effective learning in terms of conditions and atmosphere as well as efforts to maintain it, the educator, as the guide, must be able to carry out the learning process optimally. Besides, to create an atmosphere and conditions that are effective in learning, there must be certain supporting factors such as the learning environment, the expertise of educators in teaching, adequate facilities and facilities as well as good cooperation between educators and students. These efforts are efforts to create and maintain conducive, optimal, and pleasant learning conditions and atmosphere so that the learning process can run effectively. Also, the learning objectives of achievement can be maximally achieved.